Comparison of the pharmacological and biological properties of HPMA copolymer-pirarubicin conjugates: A single-chain copolymer conjugate and its biodegradable tandem-diblock copolymer conjugate - Etrych, Tomáš; Tsukigawa, Kenji; Nakamura, Hideaki; Chytil, Petr; Fang, Jun; Ulbrich, Karel; Otagiri, Masaki; Maeda, Hiroshi (European journal of pharmaceutical sciences, 2017)
In this study, we compared the enhanced permeability and retention (EPR) effect, toxicity, and therapeutic effect of the conjugate of the linear polymer poly(N-(2-hydroxypropyl)methacrylamide) (HPMA) with pirarubicin with an Mw below the renal threshold (39g/mol) (named LINEAR) and the disulfide-linked tandem-polymeric dimer of the poly(HPMA)-pirarubicin conjugate with an Mw above the renal threshold (93g/mol) (named DIBLOCK). The DIBLOCK conjugate, which was susceptible to reductive degradation, showed both a better EPR effect (tumor delivery) (2.5 times greater at 24h) and a prolonged plasma half-life. In addition, DIBLOCK had a better antitumor effect, as judged by percent survival, than did LINEAR (80% vs 65% at 150days), without any apparent toxicity in an S180 tumor model. However, the LD50 value of LINEAR was slightly higher than that of DIBLOCK (50mg/kg vs 37.5mg/kg, respectively). DIBLOCK required a longer time than LINEAR to reach maximum accumulation in the tumor. DIBLOCK also showed a greater time-dependent increase in the concentration in the tumor compared with the plasma concentration.
Keywords: Chromatography, High Pressure Liquid; poločas; Humans; Drug Carriers; molekulová hmotnost; doxorubicin; renální reabsorpce; Antineoplastic Agents; biologická dostupnost; tkáňová distribuce; Doxorubicin; lidé; Half-Life; zvířata; myši; Drug Liberation; uvolňování léčiv; Mice; Biological Availability; Renal Reabsorption; Polymethacrylic Acids; biologický transport; Male; nosiče léků; nádorové buněčné linie; protinádorové látky; Animals; kyseliny polymethakrylové; Cell Line, Tumor; mužské pohlaví; vysokoúčinná kapalinová chromatografie; Tissue Distribution; Biological Transport; Molecular Weight